2023
DOI: 10.3892/ijo.2023.5567
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of multidrug resistance to chemotherapy mediated by P‑glycoprotein (Review)

Yichen Tian,
Yongrong Lei,
Yani Wang
et al.

Abstract: Multidrug resistance (MDR) seriously limits the clinical application of chemotherapy. A mechanism underlying MDR is the overexpression of efflux transporters associated with chemotherapeutic drugs. P-glycoprotein (P-gp) is an ATP-binding cassette (ABC) transporter, which promotes MDR by pumping out chemotherapeutic drugs and reducing their intracellular concentration. To date, overexpression of P-gp has been detected in various types of chemoresistant cancer and inhibiting P-gp-related MDR has been suggested. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 151 publications
0
7
0
Order By: Relevance
“… 28 , 29 , 58 P-glycoprotein facilitates drug efflux across the cell membrane and out of the cancer cell, thus providing a means by which drug resistance can develop and which provides a site where local anaesthetics can act to reduce P-glycoprotein activity and enhance chemotherapeutic agent efficacy. 63 …”
Section: Discussionmentioning
confidence: 99%
“… 28 , 29 , 58 P-glycoprotein facilitates drug efflux across the cell membrane and out of the cancer cell, thus providing a means by which drug resistance can develop and which provides a site where local anaesthetics can act to reduce P-glycoprotein activity and enhance chemotherapeutic agent efficacy. 63 …”
Section: Discussionmentioning
confidence: 99%
“…113 Overexpression of the ABC transporter P-gp has also been reported in various chemoresistant cancer cells. 114,115 Extracellular efflux of anticancer agents, including paclitaxel and cisplatin, has been implicated in playing an important role in the chemoresistance of ovarian cancer. 116 In this study, we found that deguelin did not influence the expression and function of P-gp (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…Structurally, ABC transporters have single polypeptides with two nucleotide binding domains (NBDs) and two transmembrane domains (TMDs) [65] . The SNAIL, ZEBs, and SLUG promote MDR, while VDR, ER, PXR, KLF, Gli, and Sp are also known to modulate ABC transporters [66] . The altered ABCB1 structure or drug binding, inhibition of its expression or knockout of the ABCB1 gene are the most potential strategies to overcome ABCB1-mediated drug resistance [67] .…”
Section: Abc Superfamily Transportersmentioning
confidence: 99%